PERAN GURU DALAM MENGEMBANGKAN KEMAMPUAN MEMBACA MELALUI METODE ACM (AKU CEPAT MEMBACA) PADA SISWA KELOMPOK B2 DI RA RAUDLATUL ULUM GANJARAN GONDANGLEGI MALANG - Mufarrohah; Evi Nurhalimah (Institute Agama Islam Al-Qolam Malang, 2023)
The purpose of this study was to analyze the role of the teacher and the supporting factors, inhibiting the role of the teacher at the RA Raudlatul Ulum school regarding the role of the teacher in the application of the ACM method to develop reading skills in group B2 students at RA RAudlatul Ulum Ganjaran Gondang Legi Malang. The type of research used in this study is qualitative using an action approach. The data collection techniques used are observation, interviews and documentation. The data were analyzed using data reduction, data presentation and conclusion drawing/verification. Checking the validity of the data is done by testing the credibility, transferability, dependability, and confirm ability, marking keyword ideas, studying keywords, writing down the specified model and the data that has been found. The results of this study indicate that the teacher's role in developing reading skills through the ACM method in children is in accordance with the child's attitude. In this case, it is easier for children to recognize various syllables, increase interest in reading, and be more enthusiastic in learning. Children are also very enthusiastic when reading activities through the ACM method in their learning activities.